Wages and Compensation in Ethiopia’s Industrial Parks : Evidence from a Firm Survey - Meyer, Christian Johannes (World Bank, Washington, DC, 2021)
Jobs in exporting industries tend to pay higher wages than comparable jobs in firms focused on the domestic market. In Ethiopia, where the government has pursued an ambitious industrialization agenda, systematic data on wages in industrial parks has been scarce. This note provides an overview of worker compensation using novel firm-level data. The data shows that before the Coronavirus disease (COVID-19) pandemic, a majority of industrial park firms’ base salary exceeded the cost of basic needs as measured by the local poverty line. When bonuses, overtime pay, incentive pay, and in-kind benefits are taken into account, the median monetary value of the total compensation package is roughly fourfold of the cost of basic needs. Nevertheless, there is significant variation in pay, both within and between industrial parks with 21 percent of the surveyed firms reporting a base pay below the local poverty line. Much of the variation can be explained by the different industries in which these firms operate. Although lack of reliable data on the broader labor market makes rigorous comparisons challenging, the survey data suggests that base pay in the industrial parks is comparable with pay in the labor markets surrounding the parks.